Transformation of Noodle Processing Business Productivity through the Role of Business Managers and Innovation in Bondowoso Regency - Ach. Humaidi; Nurhidayah; Muhammad Ridwan Basalama (Quantitative Economics and Management Studies, 2025)
Indonesia’s MSME sector faces growing competition and changing consumer demands. Traditional food processors must improve operational efficiency to stay competitive. However, many still rely on conventional management methods that may not meet today’s market challenges. This study examines the interrelationships between management practices, innovation adoption, and operational performance within food processing MSMEs in East Java. Using Structural Equation Modeling-Partial Least Squares (SEM-PLS), the research analyzed census data from 70 registered enterprises. Primary data were collected through validated questionnaires measuring management capabilities, innovation implementation, and performance outcomes across operational dimensions. The findings reveal significant positive relationships among all variables. Management practices demonstrate substantial direct influence on operational performance (path coefficient = 0.798, p < 0.001) while fostering innovation adoption (path coefficient = 0.504, p < 0.001). Innovation significantly enhances performance outcomes (path coefficient = 0.633, p < 0.001). Crucially, mediation analysis confirms innovation as a significant mediator in the management-performance relationship, explaining how managerial effectiveness translates into operational improvements. The model explains 63.6% of performance variance, with effect size analysis confirming large management effects on performance (f² = 1.372) and moderate effects on innovation (f² = 0.340). Results indicate that effective management creates environments conducive to innovation adoption, subsequently driving operational efficiency. The research establishes innovation as a critical mediating mechanism, suggesting enterprise development programs should integrate management capacity building with innovation facilitation to maximize outcomes.